2013
DOI: 10.1146/annurev-nutr-112912-095300
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat in Breast Cancer Survival

Abstract: Laboratory evidence suggests a plausible role for dietary fat in breast cancer pathophysiology. We conducted a systematic literature review to assess the epidemiological evidence on the impact of total dietary fat and fat subtypes, measured pre- and/or postcancer diagnosis, in relation to breast cancer–specific and all-cause mortality among breast cancer survivors. Studies were included if they were in English, had a sample size ≥200, and presented the hazard ratio/rate ratio for recurrence, diseasespecific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 57 publications
1
69
1
2
Order By: Relevance
“…Circumstantial and epidemiological evidence indicates that overfeeding and obesity constitute negative prognostic factors with regard to the incidence, progression, and therapeutic response of several human malignancies (Casagrande et al, 2014; Gilbert and Slingerland, 2013; Makarem et al, 2013). In contrast, caloric restriction and fasting have been related to positive therapeutic outcome, both in animal models (Kalaany and Sabatini, 2009; Lee et al, 2012) and in humans subjected to voluntary fasting (Lee and Longo, 2011) or bariatric surgery (Tee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Circumstantial and epidemiological evidence indicates that overfeeding and obesity constitute negative prognostic factors with regard to the incidence, progression, and therapeutic response of several human malignancies (Casagrande et al, 2014; Gilbert and Slingerland, 2013; Makarem et al, 2013). In contrast, caloric restriction and fasting have been related to positive therapeutic outcome, both in animal models (Kalaany and Sabatini, 2009; Lee et al, 2012) and in humans subjected to voluntary fasting (Lee and Longo, 2011) or bariatric surgery (Tee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The saturated fatty acid, palmitate, is a major component of the western diet and high levels of dietary intake correlate with a number of life style diseases including Type 2 diabetes and NAFLD 30, 109, 110 . Palmitic acid induces apoptosis in pancreatic β-cell lines as well as in hepatocytes 111, 112 .…”
Section: Lipofermatamentioning
confidence: 99%
“…Several observational studies have suggested that high consumption of saturated fats 32 and high-fat dairy products may be associated with an increased risk of breast cancer mortality. 3,33 One study involving 1893 women showed that high intake of high-fat dairy products (> 1 serving daily) was significantly more detrimental than an intake of less than 0.5 servings daily (HR 1.49, 95% CI 1.00-2.24).…”
Section: Fatsmentioning
confidence: 99%
“…4,35 • Dietary saturated fat, especially from high-fat dairy products, may be associated with increased breast cancer mortality. 3,32,33 • Soy products have not been found to increase breast cancer recurrence 41 and may actually reduce it.…”
Section: Dietmentioning
confidence: 99%